The Vertical Metallicity Gradient of the Galactic Disk for Mono-age Stellar Populations in LAMOST - Gaohuan Long; Haibo Yuan; Shuai Xu; Chun Wang; Ruoyi Zhang; Bowen Huang (The Astrophysical Journal)
The vertical metallicity gradient of the Galactic disk offers valuable insights into the disk’s formation and chemical evolution over time. We utilized the Large Sky Area Multi-Object Fibre Spectroscopic Telescope low-resolution spectral young stellar sample to investigate this gradient and found that it approaches zero as stellar effective temperature (or age) increases (or decreases) across various Galactocentric distances. To validate this result, we analyzed 295 open clusters younger than 3 Gyr and 976 classical cepheids within the Galactic disk. The findings confirmed that, within a given narrow age range, the vertical metallicity gradient is effectively zero. This relationship between metallicity and age supports the “upside-down” disk formation theory, as it indicates that the youngest and most metal-rich stars dominate the midplane, while older and more metal-poor stars formed at larger vertical heights and currently tend to be at these heights. Overall, our results align well with theoretical predictions, offering further insight into the chemical evolution and structural properties of the Milky Way.